Lista de sírfidos afidófagos y primeros registros de Pseudodoros clavatus y Eupeodes rojasi (Diptera: Syrphidae), potenciales agentes de control biológico en la provincia de Mendoza, Argentina - López García, Guillermo Pablo (2013)
This scientific note reports the first faunistic list of aphidophagous sirfids from Mendoza and new records of Pseudodoros clavatus Fabricius and Eupeodes rojasi Marnef, potential agents for biological control.